PENERAPAN DIVERSI PADA TAHAP PENUNTUTAN DALAM SISTEM PERADILAN PIDANA ANAK - Ellen Yolanda Sinaga (Badamai Law Journal, 2016)
Implementation of diversion by a public prosecutor children, nowadays the mechanism is based on Law of The Republic of Indonesia Number 11 Year 2012 regarding the Juvenile Criminal Justice System. Further provisions concerning the guidelines for the implementation of diversion, ordinances, and coordinate the implementation of diversion stipulated on Indonesian Republic Government Regulation Number 65 in 2015 on the guidelines for the implementation of diversion and treatment of children who are aged 12 years. But the problem until now has not drawn up internal rules to the public prosecutor in the form attorney General of The Republic of Indonesia regulation as the basic for the implementation of the mechanism reffered versioned on Indonesian Republic Government Regulation Number 65 in 2015 on the guidelines for the implementation of diversion and treatment of children who are aged 12 years. The importance of internal rules as the basic for the public prosecutor in the executing diversion, as the uniformity of implementation of the diversion by a public prosecutor children across Indonesia, in order to avoid differences in the implementation mechanisms of diversion, which is still based instruction each child’s direct leadership prosecutor, who do diversion. Further in praction, there are differences in the implementation mechanisms of diversion by a children public prosecutor in Indonesia which resulted in the implementation of the goal of diversion has not been maximally as aspired is to keep children who are dealing with the law, from the adverse effects of the criminal justice system.  Keywords : diversion, juvenile criminal justice system, public prosecutor children